1997
DOI: 10.2466/pms.1997.84.3.1011
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cognitive Style and Defensive Style

Abstract: This study examines psychoanalytic psychology, theories of cognitive style, and cognitive developmental psychology to examine the relationship between cognitive style and defensive style. A new set of cognitive styles of visual attention is formulated at the following developmental levels: (1) global, (2) local, (3) global-plus-local at the concrete operational level, and (4) global-plus-local at the formal operational level, 50 subjects were administered global-local sorting tasks, the Sentence Preference Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In contrast, students who were at Perry's relativistic level of cognitive development tended to use a wider repertoire of thinking styles, including Type II and neutral styles, apart from Type I styles. This result not only supported the predictions but also provided empirical evidence for Perry's theoretical argument about students' retreat to the dualistic way of reasoning (also, see Westreich et al, 1997). In this context, students at the relativistic level of reasoning may resort to less challenging styles, such as the local and monarchic styles.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In contrast, students who were at Perry's relativistic level of cognitive development tended to use a wider repertoire of thinking styles, including Type II and neutral styles, apart from Type I styles. This result not only supported the predictions but also provided empirical evidence for Perry's theoretical argument about students' retreat to the dualistic way of reasoning (also, see Westreich et al, 1997). In this context, students at the relativistic level of reasoning may resort to less challenging styles, such as the local and monarchic styles.…”
Section: Discussionsupporting
confidence: 74%
“…Since then, little related work has been documented. A thorough search of this topic in the PsycINFO database (known as the PsycLit until recently) resulted in two entries after the year 1989 (Solís-Cámara, 1996;Westreich, Ritzler, & Duncan, 1997). The majority of empirical studies cited found significant relationships between cognitive development and cognitive styles.…”
mentioning
confidence: 99%